Designing an accessible indoor navigation application - Guidelines of how to apply universal design when designing an indoor navigation application to help users with wayfinding - PALMGREN SÖDERSTRÖM, LINNEA; ZELMERLÖW SIGANDER, MOLLY (My University, 2021)
Navigating within large buildings, such as a hospital, can be stressful and timeconsuming, leading to a bad user experience, causing anxiety and frustration due to missed appointments. Therefore, applications for indoor navigation have recently been catching attention. In the designing of a wayfinding system for a hospital environment it is important that the application is easy to use, effective, accessible, and intuitive as the ambition is to simplify the wayfinding to allow the user to access information and help individual navigation. This thesis explores how to develop an accessible design supporting wayfinding within a complex environment, such as a hospital. With the purpose to investigate how an indoor wayfinding application can be designed to be accessible, with all users in mind, with the aim to fill the gap of the existing research regarding this subject. To attempt this, a pre-study was conducted to research previous literature within the subject of accessible and universal design, and by designing and testing an indoor navigation application for Danderyds hospital with users, with and without disabilities. Through an iterative design process, the application explored key factors and solutions to support for indoor navigation. The conducted usability testings involved both remote asynchronous and synchronous usability testing online, and synchronous usability testing on smartphones. The outcome of this thesis resulted in nine guidelines of how to design for an indoor navigation application with a universal design approach.
Keywords: accessibility; universal design; inclusive design; indoor navigation; graphical user interface; complex environments; interaction design; usability test; prototyping